PENGARUH MOTIVASI, PERSEPSI, PENGHARGAAN FINANSIAL, PASAR KERJA DAN PENGAKUAN PROFESIONAL PADA PEMILIHAN KARIR AKUNTAN PUBLIK - Warsitasari, Ida Ayu Try Surya; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 21 No 3 (2017), 2017)
Career is a process of a person in building a job or pursue a job in stages to get the maximum results or expected someone in a certain period. The selection of the right career and in accordance with the interests and talents of a person is an early stage in the formation of a career. In order for a person to choose a career in accordance with the expected he should consider the factors that affect his career selection. The accounting profession at this time has an important role for business entities, government, and society because it is considered as one of the parties who are able to contribute greatly in solving the problems they face The objective of this research is to obtain empirical evidence of the influence of career motivation, economic motivation, perception, Financial rewards, labor market considerations and professional recognition on career selection as a public accountant. The research was conducted at the Faculty of Economics and Business Udayana University. Sampling method used is purposive sampling method, while data collection method is done by using questioner. The number of research samples used were 79 respondents. Data analysis technique used is multiple linear regression analysis technique. The results of this study indicate that career motivation, economic motivation, perception, and job market considerations positively influence on career selection as a public accountant. While on the other hand, financial rewards and professional recognition have no effect on career selection as a public accountant.